Koordinasi Pemerintahan dalam Penanggulangan Peladangan Ganja pada Kabupaten Gayo Lues - Desta Ariga; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study aims to determine the coordination carried out by the Gayo Lues Regency government in overcoming cannabis cultivation, and also how the obstacles that occur when implementing coordination in tackling cannabis cultivation both between one agency and another as well as between agencies and the community and to find out the efforts made by the government. (BNNK, Polri, TNI) in tackling cannabis cultivation in Gayo Lues Regency. This research uses qualitative research using descriptive method which is carried out by means of purposive sampling. Data collection techniques were carried out by interviews and documentation studies, with informants of several employees at the Gayo Lues Regency National Narcotics Agency, Gayo Lues District Police, Gayo Lues District Military Command, community leaders and communities who live in areas prone to cannabis cultivation. The results of this research indicate that the collaboration formed by the BNN Gayo Lues Regency, the Police and the Kodim 0113 Gayo Lues has been carried out as much as possible but efforts are still needed to change the mindset of the community. The coordination carried out by the government is for preventive activities carried out by the District National Narcotics Agency (BNNK) Gayo Lues, while the Police and Kodim 0113 Gayo Lues are more concerned with law enforcement. The obstacles experienced by the government in overcoming cannabis cultivation are divided into 2 (two), namely internal constraints and external constraints.